Adjusting peanut plant density and potassium fertilization for different production environments - Cordeiro, Carlos Felipe dos Santos [UNESP]; Pilon, Cristiane; Echer, Fábio Rafael; Albas, Renato; Tubbs, R. Scott; Harris, Glendon H.; Rosolem, Ciro Antonio [UNESP] (Wiley, 2023)
Peanut pod yield and its response to fertilizer-K can be affected by the environment × plant density interaction. Research was conducted with the objective of determining peanut growth and yield response to planting density and fertilizer-K application under rainfed conditions in Brazil and irrigation in the United States. The effects of plant planting density and K fertilization were more frequent in rainfed areas, compared to irrigated environments. Peanut leaf area index (LAI) and dry matter accumulation (DM) increased with increasing plant density (mainly at 30 days after plant emergence—average increments of 70% and 80% for LAI and DM, respectively), whereas the stomatal conductance was decreased, mainly in rainfed fields. In low-K soil, the application of 50 kg ha−1 of K increased leaf K concentration (12% [Brazil], first-year area and 28% crop rotation area) and stomatal conductance in rainfed fields, resulting in greater yield (23% [1340 kg ha−1; Brazil], first-year area) at low plant density. In the irrigated fields, yield increased with plant densities up to 19 plants m−2. For rainfed crops, plant density exceeding 11 plants m−2 resulted in lower yield in the area of adequate K content in the soil. Therefore, in rainfed fields, plant density must be low to assure peanuts response to K. In irrigated environments, high plant density is less detrimental to peanut yield, but no increase is observed with plant density greater than 19 plants m−2. Additionally, there was no yield increase with the application of 50 kg ha−1 of K, in irrigated environments.